Accelerated epigenetic aging and mitochondrial DNA copy number in bipolar disorder - Fries, Gabriel R.; Bauer, Isabelle E.; Scaini, Giselli; Wu, Mon-Ju; Kazimi, Iram F.; Valvassori, Samira S.; Zunta-Soares, Giovana; Walss-Bass, Consuelo; Soares, Jair C.; Quevedo, Joao (Translational psychiatry, 2017)
Bipolar disorder (BD) has been previously associated with accelerated aging; yet, the mechanisms underlying this association are largely unknown. The epigenetic clock has been increasingly recognized as a valuable aging marker, although its association with other biological clocks in BD patients and high-risk subjects, such as telomere length and mitochondrial DNA (mtDNA) copy number, has never been investigated. We included 22 patients with BD I, 16 siblings of BD patients, and 20 healthy controls in this analysis. DNA was isolated from peripheral blood and interrogated for genome-wide DNA methylation, mtDNA copy number, and telomere length. DNA methylation age (DNAm age) and accelerated aging were calculated using the Horvath age estimation algorithm in blood and in postmortem brain from BD patients and nonpsychiatric controls using publicly available data. Older BD patients presented significantly accelerated epigenetic aging compared to controls, whereas no difference was detected among the younger subjects. Patients showed higher levels of mtDNA copy number, while no difference was found between controls and siblings. mtDNA significantly correlated with epigenetic age acceleration among older subjects, as well and with global functioning in our sample. Telomere length did not show significant differences between groups, nor did it correlate with epigenetic aging or mtDNA copy number. These results suggest that BD may involve an accelerated epigenetic aging, which might represent a novel target for treating BD and subjects at risk. In particular, our results suggest a complex interplay between biological clocks to determine the accelerated aging and its consequences in BD.